PROSPECTS AND CHALLENGES OF DIGITIZATION OF INFORMATION RESOURCES IN UNIVERSITY LIBRARIES IN ANAMBRA STATE (NAU Journal of Library and Information Science, 2022)
Digitization is simply the process of converting information into a digital (computer-readable) format. The purpose of the study was to investigate the prospects and challenges of digitization of information resources in university libraries in Anambra State. Two research questions guided the study. The research design was a survey. The population of the study comprised 38 library staff in public universities in Anambra State. No sampling was done as the population was of manageable size. Two sets of questionnaire were used for data collection. The first was titled ‘Prospects of Digitalization of Information Resources in University Libraries (PDIRUL)’ While the second was titled Challenges to Digitalization of Information Resources in University Libraries (CDIRUL)’. Data collected was analysed using mean scores. The findings of the study showed that enhanced access to information resources on the web; increase in the visibility of information resources, efficient use of web and electronic data bases; increase in the availability of information resources on the web and improvement in the efficiency of information search mechanisms were prospects of digitalization of information resources in university libraries. The study equally found that the absence of digitalization policy; inefficient supervision of the project; lack of clearly stated or specified evaluation performance measure, poor preservation of digitized content and erratic power supply were major challenges major challenges inherent in the management of digitalized content in university libraries in Anambra State. It was thus recommended amongst other things that both the commencement and management of the digitization project in public universities in Anambra State should be anchored on a well-articulated digitization policy. This is to ensure the sustainability of the project in public university libraries in Anambra State.
Keywords: Digitization; Electronic Information Resources; Electronic Databases; Print Resources; University Libries; Anambra State